-200=k+(-99)

Simple and best practice solution for -200=k+(-99) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -200=k+(-99) equation:


Simplifying
-200 = k + (-99)
-200 = k + -99

Reorder the terms:
-200 = -99 + k

Solving
-200 = -99 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-200 + -1k = -99 + k + -1k

Combine like terms: k + -1k = 0
-200 + -1k = -99 + 0
-200 + -1k = -99

Add '200' to each side of the equation.
-200 + 200 + -1k = -99 + 200

Combine like terms: -200 + 200 = 0
0 + -1k = -99 + 200
-1k = -99 + 200

Combine like terms: -99 + 200 = 101
-1k = 101

Divide each side by '-1'.
k = -101

Simplifying
k = -101

See similar equations:

| a/-4=-8 | | (6r^-1)(st)^2/12(rs)^2(t^-1) | | 5(-3y+5)= | | 3[6-(y+21)]= | | -(-x-10)=7 | | 6+6v=-3(-2v-2) | | 4g-5-3g+8= | | 22-(x+8)=5x-4 | | 5/3(9)-(-14) | | 4(h-2)=44 | | 15y-5-14y+2= | | n^2-4=45 | | 10/6•3/5 | | -13v=-11 | | 2f+7g-7+8g= | | 8rs+9rs+st= | | 7y-11-2y+7=0 | | 2*(3*r)=42 | | 2y+.05x=16 | | -r+1=-5 | | 30+25x=36x-3 | | 2x(3xr)=42 | | -68=-81+m | | 36/(-9)= | | x-(1/8)y=-11 | | 67p+25=350+25P | | 30/(-9)= | | 4af^4-4ak^4=0 | | -144+4x=54-7x | | 1/3(x)=2 | | h=1+-2gk | | -(0.79m+0.227)=-(2.09m+0.838) |

Equations solver categories